The Conservation Easement Tax Expenditure: In Search of Conservation Value - Colinvaux, Roger (Columbia Journal of Environmental Law, 2012)
Roger Colinvaux is an Associate Professor of Law, The Catholic University of America, Columbus School of Law; Legislation Counsel, Joint Committee on Taxation, U.S. Congress, 2001–2008. Copyright Roger Colinvaux. Thanks to Gordon Clay, Karin Gross, Thomas Holtmann, Gerald Korngold, Ronald Schultz, Joan Youngman, Dean Zerbe, and the participants at the Lincoln Institute of Land Policy seminar for their thoughts and comments. Thanks also to Lindsey Cloud for research assistance.